Character Education Value In Short Story “Ambe Masih Sakit” Written By Emil Amir - Asdar Asdar; A. Vivit Angreani; Nursamsili Lutfin; Hamsiah - Hamsiah (STAI Hubbulwathan Duri, 2021)
This study aims to describe the values of character education contained in the short story